ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESENJANGAN SOSIAL KELOMPOK USAHA PENGOLAHAN GARAM KONSUMSI DI KABUPATEN DONGGALA - Salmon, Salmon (Katalogis, 2015)
This study aims: 1) To analyze and determine the simultaneously impact of education, health, employment, government policy and social relations on social inequalities in the business group of table salt processing in Donggala district; 2) to analyze and determine the partially effect of education, health, opportunity, employment, government policy and social relations on social inequalities the business groups of table salt processing in Donggala. There were 80 members as the sample of this study and they are the members of 8 groups of table salt processing businesses in Donggala district. This study applied census as saturated sampling techniques so that all members of population have an opportunity to nominated as respondents. Multiple linier regression methods is used to analyze the findings. This study found that there are simultaneously and partially affect of education, health, and employment opportunities, public policy and social relations on the social inequality in the business groups of table salt processing in Donggala district.